High methane uptake from soils of low and high density radiata pine afforestations compared to herbaceous systems - De Bernardi, María; Priano, María Eugenia; Fusé, Victoria; Fernandez, María Elena; Gyenge, Javier; Guzmán, Sergio; Julianera, María (Taylor and Francis, 2020)
During a one-year period, methane (CH4) fluxes from soil were studied in a southern temperate region system using a static chamber technique. Four treatments on neighboring areas with similar environmental characteristics but different vegetation cover were considered: a natural grassland (NG), an agricultural land (AL), a low tree density radiata pine afforestation (P1 – suitable for silvopastoral use), and a dense radiata pine afforestation (P2). CH4 uptake increased in the following order: AL < NG < P1 and P2 (statistically significant differences), without differences between P1 and P2. CH4 fluxes were mainly influenced by soil water content (R = 0.78; p = .0001) and bulk density (R = 0.75; p = .0004) indicating that CH4 uptake by soils is primarily connected to methane soil diffusivity. The statistical differences of these parameters could partially justify CH4 flux differences found among treatments. However, a multiple linear regression analysis indicated that other factors such as soil temperature also control CH4 fluxes (R2 = 0.86, p≪4x10−6), and could explain temporal patterns. Results suggest that the low tree density afforestations, suitable for silvopastoral use, have a functional role (CH4 uptake) similar to that of dense forests, and could be a good option to mitigate CH4 emissions by livestock and agricultural sector.